EFEKTIVITAS PEMBELAJARAN DARING MATA DIKLAT AKUNTABILITAS PNS PADA PESERTA PELATIHAN DASAR CPNS GOLONGAN II DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SULAWESI TENGGARA - Abdul Kahar Muzakir Sinapoy (Universitas Halu Oleo, 2022)
This type of research is quasi-experimental, aiming to analyze the effectiveness of online learning for PNS Accountability training for CPNS class II latsar participants at BPSDM Prov. Southeast Sulawesi. The research sample, all participants of Latsar Group II amounted to 40 people. Collecting data using questionnaires and assignment sheets. Data analysis was univariate and bivariate, using paired T test. The results of the study found that the average pre-test 77.8 (satisfactory) and the post test 85.6 (satisfactory), there was an increase in the value of 10.02%. The results of the paired T-test obtained a significance value of 0.000 <0.05, this means that there is a significant difference in the average value of respondents, before and after online learning. It can be concluded that online learning for PNS accountability training is considered effective in achieving learning objectives. Although the online learning method has several shortcomings, but the learning objectives are considered to be achieved effectively, the researchers suggest that the online learning method for the further PNS Accountability training can be carried out in both new normal and normal conditions.